Using two ray multipath model for microwave link budget analysis. - Loyka, S. (IEEE Antennas & propagation magazine.)
A two-ray ground multipath deterministic model for worst-case fading-depth prediction in microwave link budget analysis is presented. Simple formulas, providing insight into fading depth as a function of geometrical and electrical parameters, are derived. A detailed analysis shows that, in many cases, the fading depth depends mainly on the path-clearance angle. Comparison with the Olsen-Segal model shows that both models have roughly the same path-clearance-angle factor. To the best of the authors' knowledge, this can be considered the first theoretical justification of the path elevation factor in the Olsen-Segal model